The Health Empathy Map as an instrument of reflection in a non-care teaching scenario - Sousa,Luíza Uchôa de Resende (2021)
Abstract: Introduction: The development of empathy during graduation aims at forming graduates who are more prepared to build a good relationship with their patients. The health empathy map (HEM) is an adapted tool with the purpose of developing empathy in students and future doctors using self-reflection. Objectives: To evaluate the effect of using the HEM, in the tutorial group scenario, on the empathy score measured by the Jefferson scale and in the assessment of the students’ empathic relationship with their patients. Method: This was a quasi-experimental study that used a mixed-method approach, in the explanatory plan modality carried out with 56 students from the 5th semester of the undergraduate medical course at José do Rosário Vellano University, UNIFENAS-BH. The students were divided into two groups: G1: students who used the HEM in the tutorial group (TG) strategy and G2: students who did not use HEM in the TG. All students completed a sociodemographic questionnaire at the beginning of the study and the Jefferson Empathy Scale at the beginning and the end of the study. Statistical analyses were performed comparing the JSPE-Br scores between the groups and the study phases, and the HEM content analysis was performed. Results: The global empathy score was high in all phases of the study and did not differ between the groups. The content analysis revealed that the HEM encouraged students to reflect on the patients’ conditions, based on the mainstays of empathy, and considering the reading of their narratives. The reflections ranged from the biomedical aspects to complex socio-affective perspectives. Conclusion: HEM stimulated the students’ empathic reflection in a non-care setting and was able to identify the scope of the reflections, allowing the different perspectives to be discussed.